ARTICULATING THE MARGINALIZED VOICES: SYMBOLISM IN AFRICAN AMERICAN, HISPANIC, AND ASIAN AMERICAN LITERATURE - kristiawan indriyanto (British : Jurnal Bahasa dan Sastra Inggris, 2020)
The present study contextualizes how symbolism is employed by writers of ethnically minority in the United States as an avenue of their agency and criticism against the dominant white perspective. The history of American minorities is marred with legacy of racial discrimination and segregation which highlights the inequality of race. Literature as a cultural production captures the experiences of the marginalized and the use of symbolism is intended to transform themes into the field of aesthetics. This study is a qualitative research which is conducted through the post-nationalist American Studies framework in order to focus on the minorities’ experience instead of the Anglo-Saxon outlook. The object of the study is three playscripts written from authors from Mexican-American, African-American and Asian-American to emphasize how discrimination is faced by multi-ethnic.  The finding suggests how symbolism in these literary works intends to counter the stereotypical representation of Mexican-American, aligns with the passive resistance of the Civil Right Movement and subvert binary opposition of East and West which exoticizing the East.  Keywords :  minority literature in the U.S , symbolism, post-national